Analisis Sosialisasi Edukasi Kegiatan Keselematan Penerbangan Pada Masyarakat Sekitar Bandar Udara Sultan Mahmud Badarudin II Palembang - Novita Cahya Wulandari; Dwi Agustina (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research is qualitative in nature. This research intends to understand the phenomenon of what is experienced by research subjects such as behavior, perception, motivation, action, holistically by means of descriptions in the form of words and language, in special natural contexts and by utilizing various natural methods. This research will obtain complete, accurate and justifiable data in Indonesia regarding aviation safety regulations related to the Flight Operations Safety Zone (KKOP), namely Law No. 1 of 2009 concerning aviation, Minister of Transportation Regulation Number: KM 57 of 2007 regarding the Flight Operations Safety Area around Palembang SMB II Airport, and ICAO (International Civil Aviation Organization), the 1994 Chicago convention which is a reference in international law. The results of the research are: 1) Educational socialization of aircraft flight activities in the Palembang SMB II Airport Flight Operations Safety Zone is carried out well and activities run smoothly. Each participant was given an understanding regarding the safety of flight operations in the area near the airport. And this socialization resulted in an agreement so that residents in the surrounding area comply with existing regulations. 2) Obstacles to socializing the education of aircraft flight activities in the Flight Operations Safety Area of Palembang SMB II Airport is because many people cannot attend socialization activities because they also have activities so that sometimes what is conveyed by the airport cannot be maximized and what is emphasized through RT/ RW is sometimes not optimal in its delivery so that the community lacks understanding regarding living in the Flight Operations Safety Area of Palembang SMB II Airport. 3) Efforts made to disseminate education on aircraft flight activities in the Flight Operations Safety Area of Palembang SMB II Airport are to provide understanding to residents regarding dangerous activities carried out around the Flight Operations Safety Area of Palembang SMB II Airport, then the Law that applies if violating in the Flight Operations Safety Area of Palembang SMB II Airport so that residents are afraid to commit violations.